Design Thinking Sebagai Bridge of Innovation Perguruan Tinggi dan Industri di Jurusan Teknik Elektro Universitas Maritim Raja Ali Haji (UMRAH) - Nusyirwan, Deny (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2018)
The universities as the part of a foundation of the innovations see the importance of equipping the engineering background graduates with knowledge of innovation, which is indispensable in the industrial world. Therefore, universities and industries strive to synergize to create the appropriate teaching methodes and systems without eliminating the characteristics and benchmarks of these universities which will then become the brand of the collaboration to compete with other universities in the competition of graduates in the job seek. Department of Electrical Engineering at the Faculty of Engineering Universitas Maritim Raja Ali Haji (TE FT UMRAH) has seen the importance of this matter and has applied the design thinking as a bridge of innovation between universities and industry in initiating the various innovations so it is expected that the graduates of TE FT UMRAH will be able to accelerate the innovations in the industry.